ANALYZING THE INTEGRITY OF PUBLIC ACCOUNTANT AT “CEMERLANG” PUBLIC ACCOUNTANT FIRM IN SURABAYA (PHENOMENOLOGY STUDY) - Aripratiwi, Ratna Anggraini (Faculty of Economics and Business, University of Muhammadiyah Malang, 2017)
This study aims to explore the deep meaning of the integrity attitudes that is experienced, felt, and performed by a public accountant in one of the famous KAP in Surabaya, KAP